Biofilm formation by clinically isolated Staphylococcus Aureus from India - Triveni, Alasthimannahalli Gangadhara; Suresh Kumar, Mendem; Manjunath, Chavadi; Shivannavar, Channappa T; Gaddad, Subhaschandra M (The Journal of Infection in Developing Countries, 2018)
Introduction: Staphylococcal biofilms are prominent cause for acute and chronic infection both in hospital and community settings across the world. Current study explores biofilm formation by Staphylococcus aureus isolates from clinical samples by different methods. Methodology: Standard techniques used for the characterization of S.aureus. Qualitative and quantitative biofilm formation was assessed by Congo red Agar, Tube and Microtiter plate methods. Results: A total of 188 clinical isolates of S.aureus were screened for biofilm formation and 72 (38.29%) of them were found to be biofilm producers, 34 (18.08%) strong, 38 (20.21%) moderate. The remaining 116 (61.7%) were weak/ non biofilm producers. Maximum biofilm formers were recorded in pus samples (39.06%), followed by isolates from blood (38.23%) and urine (34.61%). Statistical analysis for the formation of biofilm indicated that Microtiter plate method is the most sensitive and specific method for screening biofilm production. Conclusions: Biofilm formation is one of the influential virulence factor in staphylococcal pathogenesis and persistence. Microtiter plate and Congo red agar remain as reliable methods for the qualitative and quantitative estimation of biofilm formation. Monitoring of biofilm formation in various etiological agents will help in determining the severity of infection.